Thực trạng phát triển văn hóa chất lượng tại một số trường trung học phổ thông công lập Quận 3, Thành phố Hồ Chí Minh - Ninh, Thị Thuý Nga (Tạp chí Giáo dục, 2024)
Quality is a key factor that determines the existence and development of an educational institution, so assessing the current situation as a basis for building and developing a quality culture contributes to the formation of a school system. The management system is stable, harmonious, suitable for the environment inside and outside the school. The article introduces and analyzes a number of studies related to quality culture by domestic and foreign authors, surveys and analyzes the current situation of developing elements of quality culture in high schools, including: academic environment, social environment, humanistic environment, cultural environment, natural environment; through the results of a survey of the management staff, teachers and students at a number of public high schools in District 3, Ho Chi Minh City as a basis to help managers continue complete the implementation plans to improve and develop the school's quality culture in the current context.